2022
DOI: 10.1111/raq.12681
|View full text |Cite
|
Sign up to set email alerts
|

The ornamental fighting fish is the next model organism for genetic studies

Abstract: The fighting fish Betta splendens is a freshwater species from Thailand and other Southeast Asian countries. This fish has been domesticated for 1000 years and bred for fighting, various colours, body size and fin types for 600 years. It is one of the most important fish species cultured for the world ornamental fish market. This fish is easy to culture, highly fecund and displays great morphological diversity. Its biology has been studied for over 100 years. Recently, its compact genome and transcriptomes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 102 publications
(335 reference statements)
0
13
0
Order By: Relevance
“…Body coloration, including skin and fin coloration, varies among fish 114,115 . Coloration evolved through selection and adaptation 116 .…”
Section: Status Of Breeding Salinity‐tolerant Tilapiamentioning
confidence: 99%
See 1 more Smart Citation
“…Body coloration, including skin and fin coloration, varies among fish 114,115 . Coloration evolved through selection and adaptation 116 .…”
Section: Status Of Breeding Salinity‐tolerant Tilapiamentioning
confidence: 99%
“…Coloration evolved through selection and adaptation 116 . In aquaculture, fish colour is associated with commercial value 114,115 . In O. mossambicus , the inheritance of gold and dark skin colours in nine backcross pedigrees showed that the gold phenotype was recessive and determined by a single locus.…”
Section: Status Of Breeding Salinity‐tolerant Tilapiamentioning
confidence: 99%
“…Due to their morphological and phenotypic diversity, relatively compact genome size (~440 Mb), their ease of growth in the laboratory, and their amenability to behavioral and neurobiological experimentation, betta have become an increasingly popular organism for scientific study (Lichak et al, 2022). The recent publication of high-quality reference genomes of both domesticated and wild betta has allowed for in-depth genetic and genomic analyses of sex determination, phenotypic traits such as pigmentation, fin shape and aggression, and of the evolutionary relationships between Betta species (Fan et al, 2018;Prost et al, 2020;Wang et al, 2021Wang et al, , 2022Kwon et al, 2022;Yue et al, 2022;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the asynchronous egg fertilization resulting from a protracted mating process that can last many hours, coupled with a short interval between fertilization and cell division, as well as a thick chorion, constitute significant challenges for genetic manipulation (Valentin et al, 2015;Lichak et al, 2022). Although a few studies have successfully utilized these tools, their reported success rates have been low, and none have reported germline transmission (Wang et al, 2021(Wang et al, , 2022Yue et al, 2022). Furthermore, although plasmid DNA microinjection has been used to make transgenic commercial betta (GloFish® Betta), the more controlled and efficient Tol2-based approach has not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 30 years, many genomic resources, such as mtDNA (mitochondrial DNA) markers, microsatellites, SNPs (single nucleotide polymorphisms), as well as genotyping platforms, SNP arrays, linkage maps, bacterial artificial chromosome (BAC) libraries, physical maps, transcriptomes and draft reference genome sequences, have been developed for some aquaculture species 1–8 . These genomic resources have been applied in investigating genetic diversity, population structures, molecular parentage, mapping quantitative trait loci (QTL) for economically important traits, genome‐wide association study (GWAS) for traits, MAS, GS and GE in some aquaculture species 2,9,10 …”
Section: Introductionmentioning
confidence: 99%